Creating an LNG ready worker: British Columbia's blueprint for extraction education. (1st January 2018) - Walker, Judith
ABSTRACT: Since 2011, the government of British Columbia (BC) has focused on building the Canadian province's economy through the development of a Liquefied Natural Gas (LNG) sector. In service of this endeavour, the government launched the Skills for Jobs Blueprint, which attempts to more clearly align BC's education system with resource extraction industries. In this paper, I argue that at the heart of this policy is the idea of education for, through, and as extraction. Conceptually, 'extraction education' focuses on supply (what we can take out of the earth, institutions, and individuals) rather than demand (what is needed to put into the educational system to meet needs of the land, institutions, communities, and individuals), and is problematic on environmental, economic, employment, equity, and educational fronts. In theorising 'extraction education' I extend Freire's ideas on 'banking education' and briefly explore dialogic, problem-posing counters to it.